2017
DOI: 10.1364/oe.25.029812
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-switchable and wavelength-controllable multi-functional metasurface for focusing and surface-plasmon-polariton wave excitation

Abstract: Realizing versatile functionalities in a single photonic device is crucial for photonic integration. We here propose a polarization-switchable and wavelength-controllable multi-functional metasurface. By changing the polarization state of incident light, its functionality can be switched between the flat focusing lens and exciting surface-plasmon-polariton (SPP) wave. Interestingly, by tuning the wavelength of incident light, the generated SPP waves can also be controlled at desired interfaces, traveling along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Recently, metasurfaces (MSs) have attracted growing interests of many researchers due to their planar profile, easy fabrication, and also strong beam control capacity [1][2][3][4][5][6]. For phase gradient metasurfaces (PGMS), proposed by Yu et al [7], a wide range of applications have been found, such as anomalous beam bending [8,9], focusing [7,10], surface-plasmon-polariton coupling [11,12], and polarization manipulation. With the ability of tuning the phase range covering 2π, metasurface can be used to improve performance of antenna.…”
Section: Single-layer Broadband Planar Antenna Using Ultrathin High-ementioning
confidence: 99%
“…Recently, metasurfaces (MSs) have attracted growing interests of many researchers due to their planar profile, easy fabrication, and also strong beam control capacity [1][2][3][4][5][6]. For phase gradient metasurfaces (PGMS), proposed by Yu et al [7], a wide range of applications have been found, such as anomalous beam bending [8,9], focusing [7,10], surface-plasmon-polariton coupling [11,12], and polarization manipulation. With the ability of tuning the phase range covering 2π, metasurface can be used to improve performance of antenna.…”
Section: Single-layer Broadband Planar Antenna Using Ultrathin High-ementioning
confidence: 99%
“…By selecting the appropriate nanoantennas and arranging them reasonably, different phase gradients can be achieved independently for x ‐ and y ‐polarized waves. As an example, incident waves with x ‐polarization can be converted into SPPs while the y ‐polarized waves can be focused . Besides, the SPP waves can be excited at desired interfaces by tuning the wavelength of incidence due to the satisfaction of different Kerker condition.…”
Section: Prominent Applications In Few‐layer Metasurfacesmentioning
confidence: 99%
“…Similarly, polarization-switchable multi-functional metasurface for focusing and SP excitation are also designed by Ling et.al. [34]. All these works realize the independent SSP/SP excitation and beam steering under orthogonal linear polarization electromagnetic wave (EMW) illumination.…”
Section: Introductionmentioning
confidence: 99%